38 IDENTIFICATION OF POTENTIALLY INAPPROPRIATE MEDICATIONS IN FRAIL OLDER ADULTS RESIDING IN LONG-TERM CARE: A RETROSPECTIVE CHART REVIEW STUDY. (25th October 2022) - Heinrich, CH; McHugh, S; McCarthy, S; Donovan, MD
Abstract: Background: Deprescribing is associated with positive health outcomes for older adults in long-term care, however deprescribing is not universally implemented. This study aims to identify the most prevalent Potentially Inappropriate Medication (PIM) used among frail older adults resident in Irish Long-Term Care Facilities (LTCFs), as identified by the Screening Tool of Older Persons Prescriptions in Frail adults with limited life expectancy version 2 (STOPPFrail V2), to form the basis of a deprescribing intervention. Methods: A retrospective chart review was conducted in two publicly-funded LTCFs in the South/Southwest of Ireland ('Site 1' and 'Site 2'). Eligible participants were those: (i) ≥65 years, (ii) resident in Site 1 or 2, (iii) eligible as per the STOPPFrail v2 criteria by the site's medical officer, and (iv) receiving regular prescribed medication. Data collected included age, gender, drug, dose, frequency, regular/pro re nata and indication/relevant diagnoses. Descriptive and associative statistics were calculated. STOPPFrail was used to identify PIMs. Polypharmacy (taking ≥ 5 medications) and excessive polypharmacy (taking ≥10 medications) were calculated on the percentage of STOPPFrail eligible patients. Results: Of the 103 residents screened, 89 were eligible and included in the analysis (86%). The prevalence of frailty for residents aged ≥65 was 93.7% (n=89), polypharmacy 95.5% (n=85) and excessive polypharmacy 64% (n=57). The mean number of regular medications (standard deviation) was 10.8 (±3.8), total medications 17.7 (±5) and diagnoses 5.5 (±2.5). A significant relationship existed between the number of PIMs and the number of medicines prescribed (ρ 0.525, p<0.01). The most common PIMs were those with no clear indication, followed by the antihypertensive medications and ergocalciferol/cholecalciferol. Conclusion: Medication and PIM usage was high among LTCF residents, with inappropriate polypharmacy of concern. Potential deprescribing interventions include documenting indications for medications, incorporating routine blood pressure measurements and drug-specific guidelines to support deprescribing PIMs, reducing drug-related morbidity and medication burden.